Writing and Merriment: Gertrude Stein’s Erotics of Language - Ramalho, Maria Irene (eLyra: Revista da Rede Internacional Lyracompoetics, 2020)
As it revisits Gertrude Stein’s relationship with Alice B. Toklas – lifetime companion, collaborator, and lover – the paper shows how Stein’s writing is at the forefront of Modernism’s poetic innovation by dismantling grammar and syntax, calling into question the referentiality of language, and dealing with words as if they were sensuous objects. It concludes that Stein’s creative writing is as erotic as her love life.